Data criticality - Kaufmann, Mareile; Bonde Thylstrup, Nanna; J. Burgess, Peter; Rudinow Sætnan , Ann (STS Encounters, 2020)
The data moment, we argue, is not a single event, but a multiplicity of encounters that reveal what we call ‘data criticality’. Data criticality draws our attention to those moments of deciding whether and how data will exist, thus rendering data critically relevant to a societal context and imbuing data with ‘liveliness’ and agency. These encounters, we argue, also require our critical engagement. First, we develop and theorize our argument about data criticality. Second, by using predictive policing as an example, we present six moments of data criticality. A description of how data is imagined, generated, stored, selected, processed, and reused invites our reflections about data criticality within a broader range of data practices.